Contribution to the knowledge of the Cassidinae of Benin (Coleoptera, Chrysomelidae) - (:unkn) unknown (My University, 2020)
A first evaluation of Cassidinae is presented below, 32 species are cited, including 5 for the first time in Benin. Twenty other species are to be looked for, they are mentioned from border countries, they will probably be met very soon. The photos of all these species are figured.
Keywords: African Research